Demokrasi Dan Politik Islam: Analisis Semantik Dan Diskursif Terhadap Istilah Syūrā, ‘Adālah, Dan Khilāfah Dalam Wacana Kedaulatan Rakyat Kontemporer - Ummu Fadhilah Imran Ibrahim; Muhammad Amri; Darussalam Syamsuddin (Jurnal Ilmu Agama Indonesia, 2026)
This research investigates the development and transformation of the meanings of three central concepts in contemporary Islamic political discourse—Syūrā, ‘Adālah, and Khilāfah—which have experienced various forms of semantic change, reinterpretation, and expansion. The core problem addressed lies in the tension and overlap between their classical, normative definitions and the new meanings that have emerged as a consequence of modern socio-political dynamics. This overlap has contributed to the instrumentalization of these terms within political arenas, where they are mobilized to legitimize differing ideological positions. The study seeks to describe the processes through which these shifts in meaning occur, to identify the discursive strategies that generate renewed interpretations, and to analyze the semantic interconnections among the three concepts within the framework of modern Islamic political thought. Adopting a qualitative methodology, the research employs semantic and discourse analysis to examine both classical textual sources and contemporary writings. Data were obtained through an extensive review of Arabic linguistic scholarship, works on Islamic political theory, and modern discursive documents relevant to the topic. The findings indicate that Syūrā has evolved toward a broader and more contemporary notion of political participation; ‘Adālah has moved from being primarily an individual ethical virtue to functioning as a principle of institutional social justice; whereas Khilāfah has become increasingly politicized and fragmented in its interpretations across different ideological currents. Collectively, these three concepts form an interrelated semantic network that plays a crucial role in shaping the architecture of contemporary Islamic political discourse. The study concludes that transformations in meaning are deeply influenced by theological reinterpretations and shifting socio-political demands, thereby demonstrating the significance of semantic analysis as an analytical lens for understanding the evolution of modern Islamic political thought.